STUDY ON GENETIC VARIABILITY, CORRELATION AND PATH ANALYSIS WITH GRAIN YIELD AND YIELD ATTRIBUTING TRAITS IN GREEN GRAM [VIGNA RADIATA (L.) WILCZEK] - KUMAR, KAMLESHWAR; PRASAD, YOGENDRA; S. B. MISHRA; S. S. PANDEY; KUMAR , RAVI (The Bioscan, 2014)
An experiment was conducted on green gram to study the genetic variability, correlation among the yield components their direct and indirect effects on grain yield. On the basis of genetic variability study only 100 seed weight exhibited high heritability estimates (narrow sense) coupled with high genetic advance, indicating the preponderance of additive gene action. Selection based on this trait will be rewarding. Phenotypic coefficient of variation was slightly higher in magnitude than the genotypic coefficient of variation. Number of secondary branches per plant, number of bunches per plant, number of pods per plant, number of grains per pod, pod length and 100 seed weight had shown positive and significant correlation along with their high positive direct effect with grain yield, suggesting that these parameters may be considered as prime traits during the course of selection to have the higher potential of yield in case of green gram.